Новые виды паразитических перепончатокрылых рода Ericydnus (Hymenoptera, Encyrtidae) европейской фауны - Тряпицын, В.А. (Вестник зоологии, 1982)
Three Encyrtid species of the g e n u s Ericydnus are described: E. elizabethae sp. n. from the Crimea is similar to E. ventralis ( D a l m a n ) in having the same forewing length/width ratio, and differs from it by the presence of well developed apical membraneous scutellum flange; E. theron sp. n. is a parasite of the mealy-bug, Heliococcus bohe- micus S u l con Caragana arborescens in Moldavia, it is close to E. longicornis (Dalman) and E. heliococci Triapitzin et Herthevtzian and differs from both by yellow-brown colour of the female thorax; E. bischoifi sp. n. from Austria is similar to E. strigosus ( N e e s ) , differing from it by the lack of punctation in the median zone of frons before the anterior ocellus.